2019
DOI: 10.3892/etm.2019.7612
|View full text |Cite
|
Sign up to set email alerts
|

Lycium barbarum polysaccharide attenuates cardiac hypertrophy, inhibits calpain‑1 expression and inhibits NF‑κB activation in streptozotocin‑induced diabetic rats

Abstract: Cardiac hypertrophy is one of the key structural changes that occurs in diabetic cardiomyopathy. Previous studies have indicated that the activation of NF-κB by calpain-1, a Ca 2+ -dependent cysteine protease, serves an important role in cardiac hypertrophy. The aim of the present study was to assess the effect of 30 and 60 mg/kg Lycium barbarum polysaccharide (LBP) treatment, the major active ingredient extracted from Lycium barbarum , on ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 30 publications
2
10
0
Order By: Relevance
“…Meanwhile, there was some data manifesting that curcumin could decrease serum TNF-α levels in diabetes rats [ 36 ]. According to the results of Western blot and IHC staining in this study, we can conclude that p65 mainly works by entering the nucleus in the cerebral cortex of diabetic rats which is consistent with previous findings [ 37 ]. Similarly, curcumin or A13 could effectively reduce the level of p65 in the nucleus of diabetes rat.…”
Section: Discussionsupporting
confidence: 92%
“…Meanwhile, there was some data manifesting that curcumin could decrease serum TNF-α levels in diabetes rats [ 36 ]. According to the results of Western blot and IHC staining in this study, we can conclude that p65 mainly works by entering the nucleus in the cerebral cortex of diabetic rats which is consistent with previous findings [ 37 ]. Similarly, curcumin or A13 could effectively reduce the level of p65 in the nucleus of diabetes rat.…”
Section: Discussionsupporting
confidence: 92%
“…Meanwhile, there was some data manifesting that curcumin could decrease serum TNF-α levels in diabetes rats [36]. According to the results of Western blot and IHC staining in this study, we can conclude that p65 mainly works by entering the nucleus in the cerebral cortex of diabetic rats which is consistent with previous ndings [37]. Similarly, curcumin or A13 could effectively reduce the level of p65 in the nucleus of diabetes rat.…”
Section: Discussionsupporting
confidence: 89%
“…LBP, a member of the Solanaceae, is the major active ingredient extracted from Lycium barbarum and contains 6 monosaccharides, galactose, rhamnose, glucose, mannose, arabinose, xylose and 18 different amino acids, and exerts a large variety of beneficial effects, such as immunomodulation, anti‑inflammation and anti-aging [ 31 ]. Recently study further demonstrated that LBP attenuated cardiac hypertrophy and improved cardiac function in diabetic rats [ 32 ]. Accordingly, we speculated that LBP might play important cardioprotective roles in myocardial I/R rats by inhibiting oxidative stress.…”
Section: Discussionmentioning
confidence: 99%